Analisis Kinerja Crushing Plant Melalui Uji Beltcut Untuk Mendapatkan Persentase Hasil Produksi Yang Optimal Dan Hubungannya Dengan Production Rate Index Pada Tambang Batu Andesit Di Pt Koto Alam Sejahtera - Zuzyana Ditya Rahmi; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
PT Koto Alam Sejahtera is one private company engaged in the mining of andesite stone with open pit mining with quarry method. Located in Jorong Polong Duo Kenagarian Koto Alam District Pangkalan Koto Baru District Lima Puluh City Province West Sumatra. The purpose of this research is to analyze the performance of the crushing plant and other obstacles encountered during production activities. One of the steps to be taken so that the desired target company can be fulfilled is to rearrange the CSS (close side setting) on the cone crusher. To determine the actual capacity cone crusher then done by doing beltcut test beltcut test. Beltcut test is one type of tool capacity testing on belt conveyor, with the aim of knowing the amount (tonnase) and efficiency of the crushing plant. With the results obtained from the beltcut test, it is hoped that it can be used as a basis handliig crushing plant in the future. Currently the total production generated from the crushing result is 111,12 ton / hour or 17.574,20 ton / month, with the CSS size setting on the 45 mm for cone crusher I and 18 mm for cone crusher II. This amount is considered not able to meet the target set by the company that is as much as 23.000 tons / month in February. After the analysis, the total production was 155.98 ton/haur or 24.669,99 ton/mounth with 56 mm size of CSS cone crusher I and 26 mm for cone crusher II.Keywords: quarry method,  crushing plant, close side setting, beltcut test, efficiency